Crisis Management: Theory and Practice (IntechOpen, 2018)
Crisis management is an interdisciplinary subject field represented by theoretical problems, practical activity, people management and the art of crisis situation solving. Overall, the studies that this publication contains are to provide an overview of the state of the art mainly focused on crisis management cycle represented by certain phases and steps. Topics include also lessons learned from natural and man-made disasters, crisis communication, information systems in crisis management, civil protection and economics in crisis management. We hope that chapters of this book will provide useful information within crisis management issue for a wide audience.